2020
DOI: 10.5505/pajes.2019.80850
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of brewery waste

Abstract: Atık yönetimi, biracılık sektörü de dahil olmak üzere tüm gıda endüstrisi için çevre bileşenlerinin korunması, kirliliğin önlenmesi ve ekonomik üretim için kritik bir öneme sahiptir. Çevre kirliliği, dünya nüfusundaki artış ve buna bağlı olarak daha verimli üretim yöntemlerinin geliştirilmek zorunda olması gibi nedenlerle atık ve yan ürünlerin geri kazanılması ve bu atıklardan katma değeri yüksek ürünlerin üretilmesi zorunlu hale gelmektedir. Bira üreticileri, atıkların yönetimi için ülkeler tarafından yürürlü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…According to the results of the present study, the dry matter level of the meat varied depending on the treatment sources. Since the dry matter levels of yeast and milk are 8% and 12.6%, respectively (Atalay et al., 2019 ; Gürsoy, 2010 ), it was observed that the dry matter levels of the meats treated with yeast and milk increased compared to the mineral water group. Consequently, this increase in the dry matter level can be attributed to the high quantity of dry matter in yeast and milk marinades, and possibly even to the high ability of squid meat to absorb the yeast and milk marinades.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of the present study, the dry matter level of the meat varied depending on the treatment sources. Since the dry matter levels of yeast and milk are 8% and 12.6%, respectively (Atalay et al., 2019 ; Gürsoy, 2010 ), it was observed that the dry matter levels of the meats treated with yeast and milk increased compared to the mineral water group. Consequently, this increase in the dry matter level can be attributed to the high quantity of dry matter in yeast and milk marinades, and possibly even to the high ability of squid meat to absorb the yeast and milk marinades.…”
Section: Resultsmentioning
confidence: 99%
“…The pH of the meat has an impact on the activity of the endogenous enzymes (Collignan & Montet, 1998). The pH levels of yeast, milk, and mineral water used in the present study are 4.5, 6.5, and 6.7, respectively (Atalay et al, 2019;Gürsoy, 2010).…”
Section: Proximate Compositionmentioning
confidence: 93%
“…Brewery waste is a negative cost factor for the brewery industry; its rich content of complex carbohydrates, nitrogen, and minerals is very important to the production of biotechnological products such as biofuel, enzymes, organic acids, and bioactive compounds [43].…”
Section: Results and Interpretationsmentioning
confidence: 99%